PENGEMBANGAN POTENSI KEPEMIMPINAN MELALUI OLAHRAGA FUTSAL - Fajar Dwi Farhan, - (2021)
This research is motivated by low student social skills that make children less capable develop self-potential due to the lack of opportunities or places that students get. This study aims to determine and test the futsal training program in which reminders of leadership are given to the development of student leadership potential. The method used in this study is an experimental method using a true-experimental research design with a pretest-posttest control group design. The population in this study were students who participated in futsal extracurricular activities. The sample in this study were 20 students who took part in extracurricular futsal activities. In taking the sample, the researcher used a purposive sampling technique. This study used an instrument in the form of a leadership attitude questionnaire. Keywords: leadership, futsal sport, extracurricular activities, training program.